Does Single Parenthood Increase the Probability of Teenage Promiscuity, Drug Use, and Crime? Evidence from Divorce Law Changes - Heather Antecol; Kelly Bedard; Eric Helland (Claremont McKenna College, Department of Economics, 2001)
It has long since been established that children raised by single parents are more likely to become sexually active, commit illegal acts, and use illegal drugs at young ages. What has not been determined is whether or not there is a causal effect associated with the disintegration of the family. Would these children have been more likely to participate in 'deviant' behavior even if their family structure had remained intact? This study provides evidence in favor of a negative causal impact of single-parent status. Using state-level divorce law changes to instrument for years that the biological father lives in the household, we find that youth who spend part of their childhood/youth living in a household that does not include their biological father are more likely to smoke regularly, become sexually active, and be convicted of a crime.
Keywords: J12; J13; 330; Family Structure; Marital Dissolution; Youth Outcomes